Flashcard Media Innovation in Thematic Science Lessons Growth and Development of Living Creatures in Elementary Schools - Annissa Syafarina Sari; Krisna Wijaya; Ridho Gata Wijaya (Universitas Pendidikan Ganesha, 2023)
The difficulty of the material presented in science subjects and the teacher's lack of ability to utilize learning media have an impact on students' low ability to understand learning material. So, the aim of this research is to develop flashcard media on the growth and development of creatures in elementary schools so that students can more easily understand the material being taught. The research design used is research and development (R&D) which goes through 7 stages of development design according to Borg & Gall. The data collection techniques used in this research were interviews, observation and questionnaires. The data analysis technique uses quantitative descriptive. The results of this research and development show that the flashcard learning media regarding the growth and development of living things to equip students' speaking skills is declared suitable for use. This can be seen from the results of material validation with an average score of 4.8 which is in the